Prospects for the Development of Artificial Intelligence - Levadnii, O. O. (My University, 2020)
Today, artificial intelligence and machine learning have begun to be applied in almost all areas of human activity: rom the simple technology of blurring the background in photographs to the analysis of genetic predisposition to serious medical diseases by supercomputers.
Keywords: artificial intelligence; medical diseases; machine learning